ANALISIS TINGKAT KEMATANGAN SISTEM MANAJEMEN KEAMANAN INFORMASI DIREKTORAT JENDERAL PERBENDAHARAAN DIUKUR DENGAN MENGGUNAKAN INDEKS KEAMANAN INFORMASI (STUDI KASUS: APLIKASI SPAN) - Syarif, Rifqi Akmal; Nugroho, Agung (JURNAL INFO ARTHA, 2016)
Implementation  of  Information  Security  Management  System  (ISMS)  is  one  of  the  internal control  measures  to  minimize  risk  and  information  security  threats  such  as  information  leakage, application malfunction, loss of data, and low performance of IT networks. Several incidents related to information security have already occurred in the implementation of Treasury  System and  the State Budget (SPAN) within the Directorate General of Treasury. Therefore, Directorat General of Treasury has made efforts to implement information security in accordance with Ministry of Finance Decree No. 479 / KMK.01 / 2010 on Policy and Management System Standards Information security. In this study, Index  KAMI  which  was  published  by  the  Directorate  of  Information  Security,  Ministry  of Communication and Information has been used to evaluate the maturity level of SPAN's information security. Six key areas examined in this study are the role and the importance of ICT, information security governance,  risk management,  information  security,  information  security  management  framework, management  of  information  assets,  technology  of  information  security.  The  results showed  that  the maturity level of SPAN implementation is still at Level II (basic framework implementation). Of the six key  areas  analyzed,  information  security  technology  scored  the  highest  (83%).  However, risk management still shows low score that need special attention from the Directorate General of Treasury.